Steroid Nanocrystals Prepared Using the Nano Spray Dryer B-90 - Kohji Nishida; Koichi Baba (MDPI AG, 2013)
The Nano Spray Dryer B-90 offers a new, simple, and alternative approach for the production of drug nanocrystals. In this study, the preparation of steroid nanocrystals using the Nano Spray Dryer B-90 was demonstrated. The particle size was controlled by selecting the mesh aperture size. Submicrometer steroid particles in powder form were successfully obtained. These nanoparticles were confirmed to have a crystal structure using powder X-ray diffraction pattern analysis. Since drug nanocrystals have recently been considered as a novel type of drug formulation for drug delivery systems, this study will be useful for nano-medical applications.